Penerapan Model Inkuiri Terbimbing Berbantuan Media Papan Paku Untuk Meningkatkan Aktivitas dan Belajar Siswa SD - Apriyani Zulika; Neza Agusdianita (Universitas Bengkulu, 2023)
This study aims to improve the activities and student learning outcomes by applying the guided inquiry model using nail board media in class IV B, 44 SDN Bengkulu. The research subjects were teachers and students of class IV B SDN 44 Bengkulu. The research instruments were in the form of observation sheets and test sheets. The test data analysis technique uses the average value formula and the percentage of classical learning completeness. Observation data were analyzed using the average score formula, highest score, lowest score, difference in score and range of values ​​for each criterion. The results of the average teacher activity cycle I obtained 32.25 second cycle obtained 40.25. The activity of the first cycle students got an average of 34.75 and the second cycle was obtained at 40.75. While for the average student learning outcomes for the knowledge aspects of the first cycle 78.92 with classical learning completeness 67.86% and the second cycle 83.66 with classical learning completeness 85.71%. Meticulous attitude aspect average score of cycle I 2.46, cycle II 3.01, self-confidence attitude cycle I 2.53 cycle II 3.12, discipline attitude cycle I 2.85 cycle II 3.19, and attitude of wanting know cycle I 2.73 cycle II 3, 44. Aspects of skills using the formula cycle I 2.55 cycle II 3.24, skilled at making, cycle I 2.51 cycle II 3.3, skilled in using the media cycle I 2.65 cycles II 3.22, skilled at showing the results of the first cycle 2.76 second cycle 3.3. Thus, the application of a guided inquiry model using nail board media can improve the activities and student learning outcomes in Mathematics learning in class IV B of the 44 SDN Bengkulu.